Erectile dysfunction treatment and traditional medicine—can East and West medicine coexist? - Lee, Joe K. C.; Tan, Ronny B. W.; Chung, Eric (Translational Andrology and Urology, 2016)
Erectile dysfunction (ED) is a common sexual problem affecting many men irrespective of cultures, beliefs and nationalities. While medical therapy for ED has been revolutionized by the advent of oral phosphodiesterase type 5 inhibitors and intracavernosal injection of vasoactive agents, recent technological advances such stem cell therapy, low intensity shock wave and newer generation of penile prosthesis implant offer hope to men who do not respond to conventional medical therapy. In contrast, traditional and complementary medicine (TCM) focuses on the restoration and better overall bodily regulation with the use of various herbal and animal products as well as exercises to invigorate qi (energy) in vital organs. Western medicine involves an analysis of ED symptom and underlying causes that contribute to ED, while TCM emphases the concept of holism and harmonization of body organs to achieve natural sexual life. The following article reviews our current understanding regarding the philosophical approach, and evaluates the evidence surrounding various ED therapies between mainstream Western Medicine and TCM.